(untitled) (SAARC Journal of Agriculture, 2018)
An experiment was conducted in a venyl house at the environmental stress site of Bangabandhu Sheikh Mujibur Rahman Agricultural University during September to December 2012 to know the internal water status under drought stress in soybean genotypes, viz. Shohag, BARI Soybean-6, BD2331 (relatively stress tolerant) and BGM2026 (susceptible). Drought (water) stress reduced the leaf water potential in all the genotypes though was more negative in tolerant genotypes than in susceptible ones. The lowest leaf water potential was obtained from BARI Soybean-6 (-1.58 MPa) and the highest in BGM2026 (-1.2 MPa). Relative water content (RWC) decreased remarkably in all the genotypes and reduction was more in susceptible than tolerant genotypes. At 8.00 am, RWC of stressed plants decreased by 9.58, 9.02, 8.90 and 13.90% in the genotype Shohag, BARI Soybean-6, BD2331 and BGM2026 at vegetative stage, respectively. Drought stress decreased the exudation rate in all the genotypes of soybean and it was 24, 27, 22 and 12 mg h-1 in the genotype Shohag, BARI Soybean-6, BD2331 and BGM2026 at vegetative stage, respectively. Leaf temperatures in drought stressed plant were higher than in well-watered plants. Shohag, BARI Soybean-6, BD2331 and BGM2026 showed 4.7, 4.5 5.2 and 11.07% increase in leaf temperature due to water stress. At drought stressed treatment reduction in leaf water potential, relative water content, exudation rate and water retention capacity were noticed at the three growth stages in all the genotypes with a concurrent increase in leaf temperature. Genotypes BARI Soybean-6, Shohag and BD2331 showed considerably less reduction in relative water content, exudation rate and water retention capacity, high reduction in leaf water potential and less increase in leaf temperature during drought were considered as drought tolerant. However genotype BGM2026 showed considerably high reduction in relative water content, exudation rate and water retention capacity, low reduction in leaf water potential and high increase in leaf temperature was considered as drought susceptible. SAARC J. Agri., 15(2): 163-175 (2017)